Impacto de la densificación urbana excesiva y la ocupación dentro suelos consolidados (2022)
The compact city model has guided us to a new grouping of social conditions, despite this the search for growth in height of volumetric density seems never to end, controlled planning in large cities is usually mowed down by population behaviors, over density, leaving the inhabitants without public or private spaces, thus promoting a progressive deterioration of the quality of life within cities. That is why a replicable model is proposed under four fundamental concepts that addresses the problem question: What parameters could be considered to develop a replicable model that balances free areas and occupation in consolidated cities?